Pain - related methylation driver genes affect the prognosis of pancreatic cancer patients by altering immune function and perineural infiltration - Zhang, Chencheng; Xu, Weiwei; Chen, Xudong; Wang, Xingdan; Cui, Xiaopeng; Zhao, Wenjing (Frontiers in Genetics, 2025)
BackgroundThe malignant progression of pancreatic cancer (PC) is frequently accompanied by intractable pain mediated through perineural invasion (PNI), yet the underlying epigenetic regulatory mechanisms remain elusive.This study aims to elucidate the role of DNA methylation in the pathogenesis of PC pain, including its interactive effects with the nervous and immune systems.MethodsIntegrating multi-omics data from TCGA-PAAD (Pancreatic adenocarcinoma), we identified methylation driver genes (MDGs) using the MethylMix algorithm. By intersecting MDGs with pain-related gene sets and conducting multi-step regression modeling, we established a five-gene prognostic signature (PSMB8/COL17A1/BICC1/CTRC/TRIP13). Next, in order to elucidate the underlying mechanisms, we conducted differential expression analysis, protein-protein interaction network analysis, functional enrichment analysis, and single-cell sequencing. Additionally, we quantified immune infiltration using CIBERSORT and TIMER.ResultsPain-related MDGs are enriched in immune regulation, extracellular matrix reorganization, and cation channel activity, constituting the “immune-neural axis” of epigenetic regulation. The prognostic five-gene signature significantly stratifies patient survival risk (HR = 3.83, p = 1.4e−8), with its methylation levels positively correlated with CD4+ T cell infiltration and negatively correlated with dendritic cells. Model-derived differentially expressed genes exhibited dual immune-neural tropism at single-cell resolution, prominently enriched in presynaptic signaling and synaptic vesicle cycling. Mechanistically, MDGs orchestrate pain progression through PNI-associated neural remodeling and K+ channel-mediated neuronal hypersensitization.ConclusionThis study establishes a visceral pain model centered on pancreatic parenchymal nociception rather than secondary neural effects, and for the first time proposes an interconnected regulatory network linking epigenetic modifications, immune reprogramming, and neural plasticity, revealing dual pain pathogenesis mechanisms: (1) immune microenvironment reshaping that potentiates neuroinflammation, and (2) direct ion channel regulation enhancing neuronal excitability. These findings provide a mechanistic foundation for developing methylation-based prognostic biomarkers and multimodal analgesic therapeutic strategies targeting the immuno-neural nexus.